Analysis of room attendant service quality towards guests’ satisfaction during the Covid-19 pandemic - Abdul Mu’is; Ida Ayu Elistyawati; Made Sudiarta; I Ketut Sutama (International Journal of Green Tourism Research and Applications, 2022)
This research aims to analyse room attendant service quality towards guests’ satisfaction at a 3-star hotel in Yogyakarta, Indonesia, especially at the moment of Covid-19 pandemic. The research method used are service quality and importance-performance analysis method from January until first April 2021 with 80 guest staying in the hotel. It is by measuring five dimensions of service quality: tangible, reliability, responsiveness, assurance, empathy. The results of the assessment show that the average room attendant performance is lower than the average guest expectation, so guests staying at the hotel are less satisfied with the service of the room attendant. Increasingly intense competition in the service industry makes the hotel strive to improve the quality of service in accordance with customer demand at present (short term), as well as future (long term) so that customers feel satisfied and continue to use the service.